The Digital Marketing Through Instagram to Increase Online Engagement (Virtual Ethnographic Study with Cyber ​​Media Analysis on Rotiyu's Instagram Account) - Intan Primasari; Ulfa Yuniati; Saepul Adnan (PT ARRUS Intelektual Indonesia, 2023)
The goal of this research is to analyze the effectiveness of digital marketing through Instagram in increasing Online Engagement on Rotiyu's Instagram account. This research is an ethnographic survey research conducted online. The research was conducted on the @rotiyu account which utilizes Instagram social media for digital promotion media. The types of data in this research are primary and secondary. Primary data collection was carried out using a questionnaire and the results of mechanical observations. Secondary data was obtained through literature study from various journals and articles related to research. This study uses virtual ethnography with cyber media analysis methods to find out digital marketing through Instagram in increasing online engagement. In the results of the study, researchers made categorizations to make it easier to present findings in the field, either through interviews or observational data on social media. Keywords: Instagram, Netnography, Online Engagement.